Ambiguity Attitudes of Individuals and Groups in Gain and Loss Domains - Aljoscha Minnich; Andreas Lange (Center for Economic Studies and ifo Institute (CESifo), 2023)
This study measures the differences in ambiguity attitudes of groups and individuals in the gain and loss domain. We elicit the ambiguity attitudes and ambiguity-generated insensitivity for natural temperature events. We do not find significant differences between individuals and groups in our main sample, yet higher ambiguity aversion and ambiguity-generated insensitivity results for groups in the gain when constraining the sample to groups and individuals with a better understanding of the experiment. Moreover, the group effect on the ambiguity-generated insensitivity seems domain dependent.
Keywords: C91; C92; D70; D81; D83; 330; ambiguity attitudes; group decision making; gain and loss domain